PENGARUH PELAYANAN, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA PT PRIMA LABELING - Vera; Wangdra, Yvonne (SCIENTIA JOURNAL, 2022)
Client delight is one of the matters that must be prioritized by every company. This research was made based on the goal of achieving the point of satisfaction of the customers of PT Prima Labeling. This study the point of satisfaction of the customers of PT. Prima Labeling. This have a look at goals to decide the impact of service, product quality, and promotion on purchaser satisfaction at PT Prima Labeling. The object of this research is the consumer of PT Prima Labeling. Statistics analysis used multiple linear regression evaluation. The technique in this study uses a saturated sample where the authors use as many as 104 respondents. To test the hypothesis used is the t test and F test and use SPSS software version 25. Based in the results of research that has been carried out, it has been shown that service, product quality, and promotion have a positive and significant impact on purchaser satisfaction, which sees the outcomes of the t count > t table and significant value obtained < 0,05. Service, product quality, and promotion also concurrently have a hight quality and huge relationship with the purchaser satisfaction variable, it may be visible from the calculated f value > f table and the sizeable value is < 0,05.